2021
DOI: 10.1007/s40747-021-00598-1
|View full text |Cite
|
Sign up to set email alerts
|

Green road–rail intermodal routing problem with improved pickup and delivery services integrating truck departure time planning under uncertainty: an interactive fuzzy programming approach

Abstract: This paper addresses the multi-objective optimization for the road–rail intermodal routing problem that aims to minimize the total costs and carbon dioxide emissions of the routes. To achieve high timeliness of the entire transportation process, pickup and delivery services are simultaneously improved based on the employment of fuzzy soft time windows to measure their service levels. The modeling of road–rail intermodal routing considers fixed schedules of rail and time flexibility of road to match the real-wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Future studies, however, may set a smaller number of available vehicles without requiring that all requests must be served. Last, linearization techniques may be exploited to reduce problem complexity for non-linear formulations and to improve the efficiency of solving small/medium-sized cases [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies, however, may set a smaller number of available vehicles without requiring that all requests must be served. Last, linearization techniques may be exploited to reduce problem complexity for non-linear formulations and to improve the efficiency of solving small/medium-sized cases [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers developed mathematical formulation for freight assignment, routing, investment priorities, and network resilience incorporating disruption in their model to tackle network vulnerability. Routing-based models are formulated for uncapacitated and capacitated networks, survivability of flow network under multiple arc failures [21], rerouting of coal by rail under disruption [22], and routing intermodal freight under disruption scenarios [23], hazmat transportation with random yard disruptions [24], and routing with carbon dioxide emissions consideration [25].…”
Section: Models Under Disruptionsmentioning
confidence: 99%
“…Carrone et al [21] found that the use of autonomous vehicles (AVs) in regular vehicle (RV) operation areas will reshape the transport system and greatly improve capacity utilization. Sun et al [22] raised a road-rail combined transport form to minimize the total costs and carbon dioxide emissions of the routes. The costs and carbon dioxide emissions problem can be minimized through the selection of vehicles to a certain extent; however, the high-capacity vehicles also mean greater investment in fixed assets.…”
Section: Related Workmentioning
confidence: 99%